Violation of the principle of impartiality in procedural theories of justice: Political Cartesianism vs the principle of responsibility for logical dialogue - Agudelo Zorrilla, Andrés Felipe (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
This article has the objective of delimiting the epistemological component in the reflexive inquiry of procedural theories of justice; this article describing the way in which they are exacerbated in a modus operandi that is called political Cartesianism, that is, as the cognitive search of clear and different ideas that standardize the administration of life; Later, in opposition to political Cartesianism, the possibility of regulating the inquiry about the procedures to achieve a basic structure of social justice based on the principle of logical dialogue will be proposed, as a guarantee of the first principle of a procedural theory of justice: impartiality. In this direction, the cultural and epistemic character of impartiality will be exposed, trying to rework a framework of understanding that, instead of dispensing with cultural mentalities, includes them as a dynamizing element of interaction in the procedures for choosing basic structures of Justice.